2014
DOI: 10.1186/1471-2407-14-108
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the collagen type 1 alpha 1 gene (COL1A1) as a candidate survival-related factor associated with hepatocellular carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the major causes of cancer-related death especially among Asian and African populations. It is urgent that we identify carcinogenesis-related genes to establish an innovative treatment strategy for this disease.MethodsTriple-combination array analysis was performed using one pair each of HCC and noncancerous liver samples from a 68-year-old woman. This analysis consists of expression array, single nucleotide polymorphism array and methylation array. The gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 42 publications
(36 reference statements)
1
57
0
Order By: Relevance
“…Of the dysregulated proteins linked to this pathway, 11 were upregulated and six were down-regulated. Collagen type I is transcribed from two separate genes, COL1A1 and COL1A2, both of which are methylated in association with decreased collagen expression in several human cancer cells (47,48), and bladder cancer tissues (49). Our data also showed that COL1A1, COL1A2, and COL18A1 proteins were down-regulated in bladder tumor cells compared with adjacent normal cells of bladder cancer patients.…”
Section: Comparison Of Tissue and Urine Proteomes In Bladder Cansupporting
confidence: 55%
“…Of the dysregulated proteins linked to this pathway, 11 were upregulated and six were down-regulated. Collagen type I is transcribed from two separate genes, COL1A1 and COL1A2, both of which are methylated in association with decreased collagen expression in several human cancer cells (47,48), and bladder cancer tissues (49). Our data also showed that COL1A1, COL1A2, and COL18A1 proteins were down-regulated in bladder tumor cells compared with adjacent normal cells of bladder cancer patients.…”
Section: Comparison Of Tissue and Urine Proteomes In Bladder Cansupporting
confidence: 55%
“…However, the expression levels of COL1A1 and COL1A2 in malignant tumors remain controversial. On one hand, frequent promoter methylation of COL1A1 was detected in renal cell carcinoma and hepatocellular carcinoma [9, 10], and COL1A2 was downregulated in melanoma [11], head and neck cancer [14], and bladder cancer [15]. On the other hand, COL1A1 and COL1A2 mRNA was upregulated in colorectal cancer and medulloblastoma [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have shown that COL1A1 (encoded by the collagen type 1 alpha 1 gene) has some predicative value in tumor diagnosis and prognosis where it has been found to be upregulated and downregulated in oral squamous cell carcinoma and hepatocellular carcinoma respectively. [2527] Another explanation for the observed collagen changes is the reversion of the atrophied adult thymus composed mostly of adipocytes and stroma. However, few studies have been conducted on collagen composition changes in association with the thymus.…”
Section: Discussionmentioning
confidence: 99%